Characteristics of the Impact Pressure of Debris Flows. Issue 3 (21st March 2022) - Zheng, Hongchao; Shi, Zhenming; de Haas, Tjalling; Shen, Danyi; Hanley, Kevin J.; Li, Bo
Abstract: Debris flows are common geological hazards in mountainous regions worldwide. Predicting the impact pressure of debris flows is of major importance for hazard mitigation. Here, we experimentally investigate the impact characteristics of debris flows by varying the concentrations of debris grains and slurry. The measured impact pressure signal is decomposed into a stationary mean pressure (SMP) and a fluctuating pressure (FP) through empirical mode decomposition. The SMP of low frequency is caused by the thrusting of bulk flow while the FP of high frequency is induced by the collision of coarse debris grains, revealed by comparing the features of impact pressure spectra of pure slurries and debris flows. The peak SMP and the peak FP first increase and then decrease with the slurry density. The basal frictional resistance is reduced by the nonequilibrium pore‐fluid pressure for debris flows with low‐density slurry, which can increase the flow velocity and impact pressures. In contrast, the viscous flow of high‐density slurry tends to reduce the flow velocity. The peak SMPs are well predicted by the Bernoulli equation and are related to the hydrostatic pressure and Froude number of the incident flow. The peak FPs depend on the kinetic energy and degree of segregation of coarse grains. The maximum degree of segregation occurs at an intermediate value of slurry density due to the transition of flow regime and fluid drag stresses. Our results facilitate predicting the impact pressures of debris flows based on their physical properties. Plain Language Summary: Debris flows are mixtures of muddy water, sand, gravels, and boulders which move down steep mountain creeks in an uncontrolled way. They are a major threat to human life, properties, and infrastructure in mountainous regions. Debris flows commonly consist of a flow nose made of coarse‐grained particles and a flow body comprising finer‐grained and more liquefied debris. It is very important to predict their impact pressures which are significantly influenced by their flow behavior. In this study, the measured impact pressures of experimental debris flows were decomposed into several components through a signal processing method. The low‐frequency components of the signal originated from the bulk flow and the high‐frequency components were caused by the coarse debris grains. This decomposition inspired us to predict separately the pressures induced by bulk flow and coarse debris grains to obtain the peak impact pressure of a debris flow. Key Points: Stationary mean pressure (SMP) and fluctuating pressure are obtained from the measured impact pressure signals Peak SMP are predicted well with a jet model based on the Bernoulli equation The transition in the dependence of grain segregation on viscosity coincides with the transition of the flow rheology